Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kualitas Pendidikan Islam: Kajian Pustaka - Jamalulel, Habib Alwi; Firdaus, Dede Ridho; Nugraha, Enung; Mujib, Abdul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The significance of human resource management (HR) in raising the standard of Islamic education is examined in this study of the literature. This study identifies important HR practices like professional development, performance management, planning techniques, and efficient hiring that support educational advancement by looking at a variety of scientific sources. These results demonstrate that an effective HR framework raises the general level of education in Islamic institutions by promoting a favorable learning environment and assisting educators' professional development. This study emphasizes how crucial HRM is as a tactical instrument for achieving high-quality education within the framework of Islamic principles.